Exposing young children to english as a foreign language: the emerging role of world english - Rajagopalan,Kanavillil (2009)
The focus of this paper is on language acquisition by young children in contexts of societal multilingualism and what lessons can be learned from it for language learning in general. It is argued that research in this area is hampered by the fact that it is almost exclusively based on a monolingual's experience of acquiring the only language they have at their disposal. By implication, then, a multilingual person's linguistic repertoire is seen as a special case of, or a departure from, the monolingual's. The case for taking a fresh look at societal multilingualism is made by considering the phenomenon of 'World English' which, it is argued, can only be understood by approaching it as a language in the making that draws its sustenance from situations where different languages are in constant contact, influencing one another.